PENGUATAN LITERASI GIZI PADA PELATIH DAN ATLET BELA DIRI WANITA PELATDA KOTA MATARAM - Johan Wahyudi; Intan Primayanti; Baiq Satrianingsih; Kokom Supriyatnak (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service activity aims to improve the knowledge and skills of athletes and coaches in managing nutritional strategies based on extra food loading to support the performance and recovery of athletes in leading martial arts in Mataram City. The background of this activity is the low practical understanding of the importance of structured nutritional intake in supporting physical abilities, endurance, and physiological adaptation of athletes, especially female athletes who face hormonal challenges, menstrual cycles, and the risk of Female Athlete Triad (FAT). The implementation of this activity was carried out through an educational approach that included training, nutritional consultations, and demonstrations of post-exercise nutritional interventions. The material presented covered the importance of proper nutritional intake, such as high-quality protein, vitamin D, and iron, as well as the implementation of energy recovery strategies after intensive training. The method used was a Focus Group Discussion (FGD), which involved athletes and coaches to dig deeper into the challenges faced in terms of fulfilling nutritional needs and understanding the influence of physiological cycles on the performance of female athletes, especially female athletes who face the risk of Female Athlete Triad (FAT). The results of this activity showed an increase in the understanding of coaches and athletes regarding specific nutritional needs, as well as the implementation of extra food loading strategies to maximize performance and recovery. This program not only provides short-term benefits in the form of increased knowledge but also builds collective awareness of the importance of nutritional literacy in athlete development.